Role of p16 expression in preneoplastic and neoplastic lesions of cervix - Saigal, Anurita; Gulati, Anchana; Kaushik, Rajni; Dattal, Digvijay Singh (International Journal of Research in Medical Sciences, 2024)
Background: Cancer of the cervix is the leading cause of cancer among women in India. Human papilloma virus plays an important role in the causation of preneoplastic and neoplastic cervical lesions. HPV type-specific oncoproteins interact with cellular regulatory proteins resulting in upregulation of p16, a cyclin dependent kinase inhibitor. This has made p16, a valuable surrogate biomarker of HPV infection, useful in evaluating HPV associated preneoplastic and neoplastic lesions of cervix. The aim of this study was to evaluate p16 expression in preneoplastic and neoplastic cervical lesions. Methods: A total of 93 specimens diagnosed histopathologically as cervical preneoplasia and neoplasia were included in this prospective study of one year duration. Maximum cases were of Neoplastic lesions followed by preneoplastic lesions. Majority of the neoplastic lesions were Squamous cell carcinoma. Immunohistochemical (IHC) staining for p16 was performed and was scored by percentage positivity and reaction intensity. p16 positivity in neoplastic lesions was significantly (p<0.0001) higher than preneoplastic lesions. Results: Of the 93 cases, 17 (18.28%) were preneoplastic and 76 (81.72%) neoplastic lesions. In the preneoplastic group, 52.94% cases were p16 positive while 47. 06% cases revealed p16 negativity. Among the neoplastic group, 85.53% cases were p16 positive while 14.47% cases were p16 negative. Conclusions: p16 expression progressively increased with increasing grades of cervical preneoplastic and neoplastic lesions, establishing p16 as a supplementary marker for early diagnosis of cervical cancer.